(untitled) (Journal of the College of Basic Education, 2019)
The present study aims at investigating the effect of applying group work technique on developing non-English major students’ attitude towards learning English as a foreign language .Two null hypotheses have been formulated; the first hypothesis states that there is no statistically significant difference between the experimental and control group in their attitude towards learning EFL after the experiment. The second one states that there is no statistically significant difference in (pre-post questionnaire) of the experimental group students’ attitude towards learning EFL. To achieve the aim of the study, and verify its hypothesis, the researcher has applied eight week experiment. A sample of 62 students has been chosen and divided into experimental and control groups. It has been chosen randomly from the second year students in the Basic Education College/ Department of History/Academic year (2017-2018). The attitude questionnaire for both groups was applied before and after the experiment. After processing the results statistically, it was found that there is a statistically significant difference in favor of the experimental group. Having used the t-test formula, it was found that there is statistically significant development in the experimental group students’ attitude towards learning EFL, which in turn indicates that the use of GWT is more effective than the traditional method. Conclusion and recommendations were drawn.